2021
DOI: 10.3390/ijerph18041712
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Characteristics by Weight Loss and Engagement in a Digital Intervention Supporting Self-Management of Weight

Abstract: There is substantial variability in weight loss outcomes. Psychosocial characteristics underlying outcomes require better understanding, particularly on self-managed digital programs. This cross-sectional study examines differences in psychosocial characteristics by weight loss and engagement outcome, and which characteristics are most associated with weight loss, on a self-managed digital weight loss program. Some underexplored psychosocial characteristics are included, such as flourishing, or a sense of mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…It is possible that the factors driving individuals to successfully achieve certain levels of weight loss influence their engagement as well. We previously demonstrated that 5% or more weight loss on Noom was associated with psychosocial characteristics such as mental health quality of life and perceived work-life balance [ 33 ], and a systematic review reported that weight loss is associated with the expectations individuals have for their weight loss [ 14 ]. Future research should separate out the individual components involved in losing certain amounts of weight loss and investigate how each relates to engagement.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the factors driving individuals to successfully achieve certain levels of weight loss influence their engagement as well. We previously demonstrated that 5% or more weight loss on Noom was associated with psychosocial characteristics such as mental health quality of life and perceived work-life balance [ 33 ], and a systematic review reported that weight loss is associated with the expectations individuals have for their weight loss [ 14 ]. Future research should separate out the individual components involved in losing certain amounts of weight loss and investigate how each relates to engagement.…”
Section: Discussionmentioning
confidence: 99%
“…However, there could be other variables that we did not capture, such as socioeconomic factors, that may be associated with 18-month weight loss. In a previous study, socioeconomic factors such as income and education did not emerge in a stepwise regression as important factors associated with weight loss at 4 months on Noom [6]. However, one study found that socioeconomic factors are associated with maintenance of long-term weight loss [70].…”
Section: Discussionmentioning
confidence: 88%
“…Body weight loss of 5-10% can reduce the risk of these conditions [4]. It is estimated that many individuals use commercial programs, but there is little knowledge on how dietary quality or nutrition knowledge is impacted via these programs [5,6]. Most studies on nutritional factors in weight loss have taken place in non-commercial settings, such as clinical trials or free-living settings [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that men are not a homogeneous group; their constructions of masculinity are shaped by a variety of sociodemographic factors, which create and reflect disparities in outcomes (Bridges & Pascoe, 2014; Galdas, 2009; Thorpe et al, 2015). However, we focus here on hegemonic masculinity given that it likely influences the Western, middle-aged users on this type of program (Evans et al, 2011; Mitchell et al, 2021). It is unclear what men would find most effective in a self-directed commercial program.…”
Section: Studymentioning
confidence: 99%